Molecular phylogeny of the Palaearctic butterfly genus Pseudophilotes (Lepidoptera: Lycaenidae) with focus on the Sardinian endemic P. barbagiae - Valentina Todisco; Andrea Grill; Konrad Fiedler; Brigitte Gottsberger; Vlad Dincă; Raluca Vodă; Vladimir Lukhtanov; Harald Letsch (BMC Zoology, 2018)
Abstract Background The Palaearctic butterfly genus Pseudophilotes Beuret, 1958 (Lycaenidae: Polyommatinae), that today occurs in North Africa and in Eurasia, includes ten described species with various distribution ranges, including endemics such as the Sardinian P. barbagiae. Phylogenetic relationships among these species are largely unresolved. In the present study, we analysed 158 specimens, representing seven species out of ten described in the genus, from widely distributed sites throughout the western Palaearctic region, using nuclear markers (28S rRNA, wingless, Internal Transcribed Spacer 2 and Elongation Factor 1α) and the barcoding region of the mitochondrial cytochrome c oxidase subunit 1 gene to investigate if the current taxonomic entities match the phylogenetic pattern. Further, we attempt to infer the geographic origin of the genus Pseudophilotes and estimate the timing of its radiations, including the split of the Sardinian endemic P. barbagiae. Results Maximum Likelihood and Bayesian inference analyses confirmed the monophyly of the genus Pseudophilotes and clearly supported the closer affinity of P. barbagiae to the species assemblage of P. baton, P. vicrama and P. panoptes as opposed to P. abencerragus. The currently accepted species P. baton, P. vicrama and P. panoptes turned out to be weakly differentiated from each other, while P. bavius and P. fatma emerged as highly distinct and formed a well supported clade. The split between the lineage comprising bavius and fatma (sometimes treated as a distinct genus, Rubrapterus) with Salvia species as larval host plants, and the remaining Pseudophilotes that utilize Thymus and other Lamiaceae (but not Salvia), dates back to about 4.9 million years ago (Mya). Conclusions Our results show that the last common ancestor of the genus probably lived in the Messinian period (5.33–7.25 Mya). At species level, they support the current taxonomy of the genus, although P. panoptes, P. baton and P. vicrama display complex patterns based on phylogeographic relationships inferred from mtDNA. The Sardinian endemic P. barbagiae turned out to be a young endemic, but clearly with European instead of North African origin and evolved through allopatric isolation on the island of Sardinia only about 0.74 Mya.